Respuesta :
Answer:
The correct answer is C. 9 -√ 105/ 2, 9 + √ 105/ 2
Step-by-step explanation:
Let's find the solutions for the quadratic equation:
x² = 9x + 6
x² - 9x -6 = 0
Using the quadratic formula, we have:
x = [- (-9) +/- √ (-9)² - 4 * 1 * -6]/2 * 1
x = [ 9 +/- √ (81 + 24]/2
x = [ 9 +/- √ (105]/2
x₁ = [ 9 + √ (105]/2
x₂ = [ 9 - √ (105]/2
The correct answer is C. 9 -√ 105/ 2, 9 + √ 105/ 2
Note: Same answer than question 14133688, answered by me today.
Answer:
x = 9+√105/2 or 9-√105/2
Step-by-step explanation:
Given the quadratic function x² = 9x+6
Re arranging we have;
x²-9x-6 = 0
Comparing this equation to general form ax²+bx+c = 0;
a = 1, b = -9, c = -6
Using the general formula to find x.
x = -b±√b²-4ac/2a
x = -(-9)±√81-4(1)(-6)/2
x = 9±√81+24/2
x = 9±√105/2
x = 9+√105/2 or 9-√105/2